Manajemen konflik warga Sukoharjo dalam menyelamatkan lingkungan terhadap pencemaran udara dan air oleh PT. RUM - Marliana Eka Fauzia; Elfrida BR. Silalahi (Universitas Merdeka Malang, 2021)
Writing about conflict management is based on the presence of waste pollution both air and water in Ngunter District, Sukoharjo Regency. The pollution waste is in indication of PT RUM, which operates in the field of industrial fiber rayon. Based on this, the author aims to determine the model or method conflict management for Sukoharjo residents regarding waste issues with PT RUM. As a conceptual basis, the writer uses conflict theory and conflict management. Whereas for method study author uses qualitative descriptive as well as with the model research the data using the study of literacy. The results of this study indicate that conflicts that occur between PT RUM and citizens sub district Ngunter , District Sukoharjo including conflict of objectives, things have views of the causes of conflict due to social factors. Factor socially the views of the many people who Felt the pollution of waste that is suspected of PT RUM thus causing the quality of water and air decreases and also attacked the health of the people around. In the process of settlement of conflict pollution environment is resident Sukoharjo get the support of the third well of the institution of government in spite of non- governmental. Government agencies such as the Regent, DPRD, KLHK, and Kominfo . While the institution of non-governmental as well as LBH Semarang, Komnas HAM and Ombudsmen. So the management of conflict is expected to Minimize losses with the conflict that. In addition it is also a model of management of conflicts of citizens Sukoharjo can be said integrative since the onset of the conflict on the outside of the will of the citizens.